Interpersonal Communication Patterns of Caregivers in Increasing the Self-Confidence of Foster Children at Al-Jam'iyatul Washliyah Orphanage - Nisa Adelia Putri (Indonesian Journal of Communication and Social, 2025)
The orphanage has a large number of foster children of different ages. The orphanage strives to provide good care and upbringing for all the children in the orphanage. The residents of the orphanage are filled with children with an age range of 10-17 years. One form of activity in increasing self-confidence is the lecture method. This lecture activity itself is a forum for children to train self-confidence, and hone knowledge about Islam at the Al-Jam'iyatul Washliyah Orphanage. The purpose of this study was to determine the interpersonal communication patterns of caregivers in increasing the confidence of foster children at the Al-Jam'iyatul Washliyah Komad II Orphanage. The research method used is qualitative research method. Data collection techniques using interviews and documentation. The research informants in this study were caregivers of children at the Al-Jam'iyatul Washliyah Komad II Orphanage. The results of the study explain that the communication patterns carried out by caregivers at the Al-Jam'iyatul Washliyah Komad II Orphanage in increasing children's self-confidence are carried out by face to face methods which consist of several methods, such as linear methods, namely by conducting lectures at every magrib or at certain times which contain motivation and support to children to increase their self-confidence. Then other communication patterns are carried out by interactive methods, meaning that caregivers invite children who have low self-confidence to a room to share and create small groups in order to monitor and understand children's problems related to self-confidence.